Pendant isocyanate and epoxide-containing copolymers: synthesis, sequential dual-functionalization with amines, and surface modifications - Demirbilek, Nisa; Cengiz, Nergiz; Gevrek, Tugce N. (Taylor & Francis Inc, 2023)
Polymers carrying different reactive groups that can be orthogonally functionalized are desirable for the design of multi-functionalizable materials. While several orthogonally functionalizable polymers have been reported, most of the work utilizes handles that are reactive toward different functional groups. However, examples of polymers that are orthogonally reactive toward molecules bearing the same functional group are rare. In this work, we report polymeric materials that can be sequentially functionalized using different amine-bearing molecules. Herein, we synthesized isocyanate and epoxide group containing copolymers, and investigated their sequential functionalization with amine-containing molecules. We show that such copolymers can be first functionalized with a particular amine-bearing molecule at room temperature, using conjugation through the isocyanate group. Thereafter, a different amine-containing molecule can be attached through the epoxy-amine reaction at 65 degrees C. Chemical characterizations of parent and subsequently functionalized copolymers were done by 1H NMR and FTIR spectroscopy techniques, to establish orthogonal functionalization. Additionally, the epoxide side chains were utilized as surface anchoring group after the functionalization of the polymer via isocyanate-amine reaction. This straightforward approach for obtaining orthogonally reactive amine-functionalizable copolymers, and surfaces derived thereof, would be attractive materials for various biomedical applications.
Keywords: Isocyanate-amine; epoxy-amine; orthogonal functionalization; functionalizable polymers; polymeric coating